Stability of Three Different Galenic Liquid Formulations Compounded from Tablet Containing Glibenclamide - Di Folco, Ugo; Falco, Daniela De; Marcucci, Fabio; Nobili, Graziella; Moretti, Vincenzo; Gioventù, Giorgio; Tubili, Claudio (Journal of Nutritional Therapeutics, 2013)
The suspensions of sulfonylurea glyburide (glibenclamide) are compounded extemporaneously for patients suffering from transitional and Permanent Neonatal Diabetes mellitus (PND). The purpose of this study is to compare the stability of three different galenic liquid formulations compounded from tablet containing glibenclamide. The samples were stored at refrigerated (2-8°C) and room temperature and analyzed at different times. All formulations analysed are stable for at least 90 days, but only two guarantee the administration responding to prescription, especially when it comes to giving dosages very small.